Australia and New Zealand Transplant and Cellular Therapies (ANZTCT) position statement: COVID‐19 management in patients with haemopoietic stem cell transplant and chimeric antigen receptor T cell. Issue 1 (24th January 2023) - Perram, Jacinta; Purtill, Duncan; Bajel, Ashish; Butler, Jason; O'Brien, Tracey; Teh, Benjamin; Gilroy, Nicole; Ho, Phoebe J.; Doocey, Richard; Hills, Thomas; Perera, Travis; Douglas, Genevieve; et al.
Abstract: Patients with post‐haemopoietic stem cell transplant or chimeric antigen receptor T ‐cell (CAR‐T) therapy face a significant risk of morbidity and mortality from coronavirus disease 2019 because of their immunosuppressed state. As case numbers in Australia and New Zealand continue to rise, guidance on management in this high‐risk population is needed. Whilst we have learned much from international colleagues who faced high infection rates early in the pandemic, guidance relevant to local health system structures, medication availability and emerging therapies is essential to equip physicians to manage our patients optimally.